Evidence Of Astrocytic Reactivity During Vestibular Compensation - Lee, Su Ann (2003)
Vestibular compensation is the spontaneous disappearance of postural and oculomotor imbalance exhibited by the vestibular system in response to decreased inputs from the labyrinths. Astrocytes in the vestibular nuclei have been reported to have a role in the plasticity of the central nervous system. The present study was conducted to investigate the behavioural changes of mice and the morphological changes and distribution of astrocytes following unilateral labyrinthectomy. Thirty-five mice (Mus musculus) underwent unilateral labyrinthectomy (UL) and fourteen underwent sham-operation. Their behavioural changes following surgical removal of labyrinths, or sham-operation, were observed. The UL groups displayed behavioural changes including head tilt, circular walking, barrel-rolling and extension and flexion of limbs. These behavioural symptoms disappeared within approximately 3 hours. For the sham-operated animals, these symptoms were absent.